Effect of Land Clearing Activity on Environmental and Arthropods Diversity (Case Study: Jati Agung, Lampung) - David Septian Sumanto Marpaung; Nova Anika; Yazid Bindar (School of Postgraduate Studies, Diponegoro Univer, 2021)
Agricultural activity relies on soil as their growth media. Besides agricultural activity, other living species also needs soil as their ecosystem. However, the biodiversity and environmental factor are often neglected in agricultural activity. Therefore, the investigation of environmental and biodiversity changes is important. In this study, the environmental parameter and biodiversity changes was investigated in area after land clearing activity. The pH was increased from in 3 times measurement. Besides, the soil temperature and air temperature was also increased in 3 times measurement between pre- and post-treatment. The soil temperature ranges from 26.2 oC to 33.2 oC in pre-treatment and 27.6 oC to 31.8 oC in post-treatment. The air temperature was observed ranges from 27.96 oC to 34.3 oC in pre-treatment and 28.36 oC to 34.56 oC in post-treatment. Measurement of RH was resulted ranges from 61.2% to 75.4% in pre-treatment and 61.4% to 74.8% in pre-treatment. The land is proposed become paddy field for next step land processing. As result, the diversity index was decreased in pre- and post-treatment. The Shannon diversity index was decreased from 0.81 to 0.72. Similarly, the Simpson diversity index was also decreased from 1.94 to 1.77. Meanwhile, the evenness index was increased from 0.58 to 0.65. These results suggested for farmer to process the land as soon as possible after land clearing process, if they want to form paddy field from pasture land.AbstrakKegiatan pertanian bergantung pada tanah sebagai media tumbuh suatu tanaman. Selain kegiatan pertanian, organisme hidup lain juga bergantung terhadap tanah sebagai ekosistem. Namun, seringkali biodiversitas dan faktor lingkungan diabaikan dalam kegiatan pertanian. Oleh karenanya, indentifikasi perubahan lingkungan dan biodiversitas sanget perlu dilakukan. Dalam penelitian ini, perubahan parameter lingkungan dan biodiversitas diamati sebelum dan sesudah aktivitas land clearing. Hasil pengamatan menunjukkan, pH tanah, suhu tanah dan suhu lingkungan meningkat dalam 3 kali pengukuran dari sebelum ke sesudah aktivitas land clearing. Suhu tanah berkisar 26.2 oC-33.2 oC pada sebelum kegiatan land clearing dan 27.6 oC-31.8 oC setelah aktivitas land clearing. Suhu lingkungan ditemukan berkisar 27.96 oC-34.3 oC pada kegiatan sebelum land clearing dan 28.36 oC-34.56 oC setelah kegiatan land clearing. Hasil pengukuran RH lingkungan ditemukan berkisar 61.2%-75.4% pada kegiatan sebelum land clearing dan 61.4%-74.8% setelah kegiatan land clearing. Sementara itu, index diversitas ditemukan menurun setelah aktivitas land clearing. Nilai Shannon diversity index ditemukan menurun setelah aktivitas land clearing dari 0.81-0.72. Pola serupa ditemukan pada nilai Simpson diversity index, dimana terjadi penurunan dari 1.94 menjadi 1.77. Nilai evenness index meningkat dari 0.58 menjadi 0.65. Berdasarkan hasil tersebut dapat disarankan ke petani untuk segera mengolah lahan tersebut setelah kegiatan land clearing untuk menghindari terjadinya pertumbuhan kembali vegetasi, serta perubahan parameter lingkungan dan biodiversitas.